Analisis Respon Pengusaha Konstruksi terhadap Beroperasinya Bank Syariâah - ., Hardiwinoto (Jurnal Ilmu Ekonomi ASET, 2010)
The aim of the research was to analyze empirically about factors influencingentrepreneurs attitude to respond the operating syariâah bank round Semarang and Demak.There were two variables, the first was dependent variable means entrepreneur attitude andthe second was independent variables which had three understanding level. There are theunderstanding level of religion (religiousity), financial mechanism of syariâah bank, andsyariâah bank product. The population in research was the member of GAPENSI (AlianceExecutor of Contruction National Indonesia) Semarang and Demak. There were the directorsor the company head who has authority in making financial decision. The method used in thishypothesis examination was linear regresion to test the independent variables influence todependent variable. The result of research indicat that result of F count equal to 19.384 atlevel of significancy 0.000 by together. While each independent variable had own significancylevel of religiousity significance 0.926 accepted at trust boundary 0.10, financial mechanismof syariâah bank significance 0.022 accepted at trust boundary 0.05, and syariâah bank productsignificance 0.001 accepted at trust boundary 0.001.Keywords: entrepreneur attitude, religiousity, financial mechanism of syariâah, syariâah bankproduct.